Conversations Around Design Sketches: Use of communication channels for sharing mental models during concept generation - Nik Shahman Nik Ahmad Ariff; Petra Badke-Schaub; Ozgur Eris (2012)
In this paper, we present an exploratory protocol study on the use of different communication channels during design sketching. We focus on how individual designers share their mental models with other designers in a group, and analyse their use of graphical, textual, and verbal communications during concept generation. Our findings suggest that verbal communication plays a role in the sharing of individual mental models during sketching, and complements graphical and textual communication channels. However, design teams can still function without verbal communication in that respect, and address design problems. They seem to compensate for the absence of the verbal communication channel by using the graphical and textual channels more, and by relying on a somewhat different communication structure. A natural and arguably more desirable interaction utilises all three channels in conjunction. Our findings also suggest that, when working in groups, designers develop and share individual mental models not only about the design task at hand but also about the design process in order to manage the group interactions